Do universities train entrepreneurs? - Cristóbal Fernández Robin; Diego Yáñez; Paulina Santander (Actualidades Investigativas en Educación, 2020)
Higher education has a deep impact on the diversity and success of entrepreneurs. It is clear that educated entrepreneurs have an advantage over other entrepreneurs given their specialized knowledge. However, the effect of higher education on entrepreneurial intention has been less studied. Does higher education or the subject imparted affect the intention to start a business? This article proposes a model that adds two exogenous variables to the Theory of Planned Behavior. The first variable is formal education in entrepreneurship represented by Subject and Entrepreneurship, and the second one is the entrepreneur environment, represented by University and Entrepreneurship. The model analyzes both variables and their impact on Attitude and Perceived Control. Data for this quantitative study is collected from an online semi-structured questionnaire by 583 university students during October and November 2014. The reliability of the scales was assessed using Cronbach Alpha, while the model was tested using structural equations. Our results confirm that university’s entrepreneurial environment, as well as the subjects studied, do have an effect on entrepreneurial intention through attitude. Additionally, the influence of both variables through the Perceived Control was not significant. Consequently, higher education must go beyond theory and focus on fostering an environment that encourages and raises awareness of entrepreneurship.